Usability of ChatGPT in the english essay writing proficiency of the BEED students - Aglibot, Karl Alvin; Tomines, Edrian Mark; Talaman, Janel; Soguilon, Janabeth; Bongolto, Rowena; Abayon, Rhona Marielle (Journal of Science and Education (JSE), 2024)
The advancement of AI technology, especially in language processing systems like ChatGPT, creates opportunities for students to elevate their writing skills. This study aimed to explore the relationship between the usability of ChatGPT and the English essay writing proficiency of the BEED students. The study utilized a descriptive correlational design to investigate the relationship. A sample of 58 participants was selected to write an essay with the assistance of ChatGPT. Researchers developed and employed a rubric to assess the quality and ethical use of ChatGPT. Then, the participants answered the USE questionnaire to measure their perceived usability of ChatGPT. The result revealed that BEED students perceived ChatGPT as beneficial in enhancing their essays and found the system easy to use, and learn, and provided satisfying results. The participants also expressed a strong sense of contentment regarding using ChatGPT. The essay writing proficiency assessment revealed that BEED students were proficient writers. However, a Pearson correlation coefficient of 0.042 showed a statistically significant but very weak relationship observed between ChatGPT usability and English essay writing proficiency levels. It can be concluded that ChatGPT may improve students' essay writing proficiency to a minimal extent. Moreover, this study recommended further research to explore ChatGPT's use in other academic outputs, refine the rubrics to include vocabulary, grammar, and sentence structure criteria, and provide training for effective AI tool management among students. Also, policymakers should establish clear policies and guidelines to ensure the responsible and ethical use of ChatGPT, maintaining academic integrity and enhancing writing proficiency.